Isolation, Amplification Approaches of Human Pokemon gene (ZBTB7) and Incorporation into Yeast Vector (Indian Journal of Forensic Medicine & Toxicology, 2020)
The transcription repressor protein ZBTB7 (FBI1, BTB-ZF protein LRF) known as a Pokemon is criticalfactor in oncogenesis which is encoded by ZBTB7 gene. ZBTB7 processes by controlling the pathways thatare required to transform normal cell to cancerous one. It produces its effects by repressing the function ofother proteins including a tumor suppressor protein ARF leading to lymphomas and other oncogenic effectsand present in very high level in certain type of B cell. So the structural study of the translation product ofthis gene is an important task to know about the carcinoferous effect of ZBTB7 along with their interactivepattern with co-repressor which prone transcription repression by stopping the activity of transcriptionfactors. In the present project DNA binding domain of ZBtB7 gene’s cDNA is developed and cloned intosuitable yeast vector.